Pemberdayaan Kelompok Wanita Tani dengan Produktivitas dan Peluang Usaha melalui Pelatihan Abon Lele di Kabupaten Sleman - Prasetyo, Satria Iman; Nugroho, Aris Widyo (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
Abstract: This empowerment program aims to increase productivity and open business opportunities for the Women Farmers Group (KWT) through training in processing catfish floss in Padukuhan Soromintan. KWT problems, such as the lack of processed agricultural products and difficulties in marketing their harvests, have caused the low productivity of the KWT Mugi Lancar to be the reason for the intense business productivity. Based on this, this empowerment conceptualizes the program as a follow-up to solving the problems faced by KWT Mugi Lancar through training in processing catfish floss. The implementation method has five stages: problem identification, conceptualization, success indicators, validation, and application. The results of the implementation of community empowerment show that the catfish floss processing training is divided into two types of exercise, namely theory and practice, which includes training on catfish floss processing, packaging, and legality submissions to marketing. The result shows a level of understanding of the catfish-shredded training participants. This is expected to increase the motivation of KWT Mugi Lancar to carry out business productivity through processing catfish floss. Abstrak: Pengabdian masyarakat ini bertujuan untuk meningkatkan produktivitas dan membuka peluang usaha Kelompok Wanita Tani (KWT) melalui pelatihan pengolahan abon lele di Padukuhan Soromintan. Minimnya olahan hasil pertanian dan kesulitan dalam memasarkan hasil panen menyebabkan rendahnya produktivitas usaha KWT Mugi Lancar. Berdasarkan hal tersebut pemberdayaan ini mengkonseptualisasikan program sebagai tindak lanjut untuk menyelesaikan permasalahan yang dihadapi oleh KWT Mugi Lancar melalui pelatihan pengolahan abon lele. Metode pelaksanaan dilakukan melalui lima tahapan di antaranya identifikasi masalah, konseptualisasi, indikator keberhasilan, validasi, dan aplikasi. Hasil akhir menunjukkan peningkatan motivasi KWT Mugi Lancar dalam produktivitas usaha melalui pengolahan abon lele.